The Implication of Symbolic Function of Jonah on Modern Culture. - Pokaew, Vajra; Forg, Florian (Saengtham College Journal, 2021)
Amid the Modernity world that started to come up since the 18th century, the meta-narrative of things that consists of the objective truth was refused and replaced with the idea of subjectivity, so the truth of modernity, especially in the religious circle, became relative to those who are carrying out the hermeneutical processes. This Independent Study aims to study the book of Jonah, which is one of the Prophetic books in the Christian Bible’s Old Testament. It contains the story of Jonah, a reblliousbehaving prophet of Israel who refused the calling from God to go to and preach against the gentile Ninevites and many strange events such as Jonah’s swallowed and stayed alive in the stomach of a great fish or the too quick conversion to repentance of Ninevites. In this study, the author seeks to find a sound meaning for Jonah in the Modern-day world by considering the functions of symbols in the text and endeavors in giving the implication of them to the modern-day church.